2003
DOI: 10.1093/bja/aeg259
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of isoflurane and propofol–fentanyl anaesthesia in a swine model of asphyxia

Abstract: Although TIVA is less prone than isoflurane anaesthesia to primary cardiovascular depression leading to asphyxia, TIVA is associated with reduced effectiveness of CPR in which resuscitation because of asphyxic haemodynamic depression occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Anaesthesia was maintained with 100-125 mg kg À1 min À1 of propofol (Diprivan 1 ) delivered by a Baxter syringe pump. Compared with other anaesthetic regimens, total intravenous anaesthesia with propofol is less likely to cause cardiovascular [7] or pulmonary [8] dysfunction, and less decrease in arterial or mixed venous oxygen partial pressure [9], in swine. Inhalation anaesthetics such as halothane may not have been appropriate for these studies, since muscle-cell damage (as indicated by increased creatine phosphokinase [CPK]) can result from such use [10].…”
Section: Anaesthesia and Experimental Set-upmentioning
confidence: 95%
“…Anaesthesia was maintained with 100-125 mg kg À1 min À1 of propofol (Diprivan 1 ) delivered by a Baxter syringe pump. Compared with other anaesthetic regimens, total intravenous anaesthesia with propofol is less likely to cause cardiovascular [7] or pulmonary [8] dysfunction, and less decrease in arterial or mixed venous oxygen partial pressure [9], in swine. Inhalation anaesthetics such as halothane may not have been appropriate for these studies, since muscle-cell damage (as indicated by increased creatine phosphokinase [CPK]) can result from such use [10].…”
Section: Anaesthesia and Experimental Set-upmentioning
confidence: 95%
“…the epidural ropivacaine and a lower inspired isoflurane concentration in the AL-group. The MAP range reported for anaesthetised pigs is 9.98-13.3 kPa 13 , and for isoflurane anaesthetised pigs 9.6-11.1 kPa with the end-tidal isoflurane concentration approximately 0.85 % 6 . The values MAP reported by Riebold 13 were somewhat higher compared with the values observed in this investigation, but were similar to the values of Malavasi 8 .…”
Section: Discussionmentioning
confidence: 92%
“…Cardiovascular stability as evaluated from increases in heart rate was therefore better maintained in the ALgroup after ropivacaine epidural when subjected to abdominal surgery. The decrease in blood pressure could be regarded as an adverse effect but this should be seen in the context that the blood pressure was higher in the ALgroup compared with the A-group and that the pressures were within range of pressures reported for isoflurane-anaesthetised pigs 6,8 . Possible complications reported in humans after the combined administration of inhalation anaesthesia and lumbar epidural anaesthesia were bradycardia and hypotension 1,10,16 .…”
Section: Discussionmentioning
confidence: 93%
“…Although some studies favor intravenous maintenance of anaesthesia (9,10), in terms of safety and hemodynamic stability, one must remember that new inhaled anaesthetics such as sevoflurane offer both cardioprotection and ease of administration (11,12). A balanced approach (13) using both intravenous and inhaled agents has been proposed and probably offers the potential benefits of both techniques.…”
Section: Discussion Discussionmentioning
confidence: 99%